2018
DOI: 10.1177/1558944718797347
|View full text |Cite
|
Sign up to set email alerts
|

Intrarater and Interrater Reliability of the Soong Classification for Distal Radius Volar Locking Plate Placement

Abstract: The Soong classification is a reliable tool, both interrater and intrarater, for assessing distal radius volar locking plate placement. The classification system remained reliable despite a randomly selected, consecutive series of images and physician observers of varying levels of training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…Lutsky et al 16 used fellowship-trained upper-extremity surgeons and found an interobserver intraclass correlation of 0.78. In contrast to the study by Creighton et al, 15 this study suggests that kappa values for interobserver reliability gradually increase for each year of training. The fluoroscopic interobserver reliability increased from 0.16 for PGY3 to 0.43 for PGY4, while the radiographic reliability did not demonstrate a significant increase until PGY4 (κ = 0.50) ( Table 3 ).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Lutsky et al 16 used fellowship-trained upper-extremity surgeons and found an interobserver intraclass correlation of 0.78. In contrast to the study by Creighton et al, 15 this study suggests that kappa values for interobserver reliability gradually increase for each year of training. The fluoroscopic interobserver reliability increased from 0.16 for PGY3 to 0.43 for PGY4, while the radiographic reliability did not demonstrate a significant increase until PGY4 (κ = 0.50) ( Table 3 ).…”
Section: Discussioncontrasting
confidence: 99%
“…The use of postoperative radiographs to assess plate prominence, although demonstrated to be reliable, may not be as beneficial as intraoperative fluoroscopy because of the time at which the images are obtained. 15 , 16 Our study suggests that early postoperative radiographs contribute no significant information with respect to plate prominence in comparison to intraoperative fluoroscopy but may be beneficial when examining the loss of fixation. For fracture reduction and fixation, the value of early postoperative radiographs in the treatment of distal radius fracture fixation has been questioned, and some studies have demonstrated that these images do not change postoperative management.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations